Phytoplankton and zooplankton diversity and community dynamics in connected coastal wetlands’ ecosystems under anthropogenic pressure (SW Mediterranean Sea) - Gueroun Sonia KM (21435836) (2025)
Transitional aquatic ecosystems exhibit remarkable biological richness and serve as vital habitats, providing refuge and critical breeding grounds. However, these environments confront an array of stressors stemming from both anthropogenic activities and climate-induced changes. Within the Southwestern Mediterranean Sea, Ichkeul Lake, a UNESCO World Heritage Site, and its interlinked Bizerte Lagoon typify the challenges confronting such habitats. This study presents an up-to-date assessment of the planktonic community (phytoplankton and zooplankton) in terms of taxonomic diversity, distribution, abundance, and functional characteristics across these ecosystems. The comprehensive analysis of surveyed parameters, encompassing both biotic and abiotic factors, reveals discernible trends: a declining gradient in nutrients, turbidity, and zooplankton abundance, juxtaposed with an ascending pattern in oxygen levels, salinity, and taxa richness as one transitions from Ichkeul Lake to Bizerte Lagoon. Notably, a shift in functional traits within the phytoplankton community is evident, denoting a transition from a prevalence of mixotrophy to autotrophy from Ichkeul Lake to Bizerte Lagoon. The environmental variables, particularly nutrients, turbidity, oxygen, and salinity, observed during the winter and spring of 2016, align with phytoplankton assemblages dominated by marine mixotroph dinoflagellates and marine zooplankton. These findings signify a profound ecosystem shift in Ichkeul Lake, transitioning from a predominantly freshwater system to an estuarine regime. These observations underscore the pressing need for refined management strategies targeting Ichkeul Lake, emphasizing prudent water resource utilization and regulated discharge, especially in the context of climate fluctuations, to facilitate the restoration of the ecosystem's good status. Other Information Published in: Estuarine, Coastal and Shelf Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecss.2025.109147